The Concept of Knowledge: The Essence of Knowledge (Ilm, Hikmah, and Ayat) - Setyawan, Roby; Alwizar; Kadar M. Yusuf (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article explores the essence of knowledge from an Islamic perspective by highlighting key concepts such as ‘ilm (knowledge), ḥikmah (wisdom), and āyah (signs). Through a qualitative approach and literature review, this study examines how the Qur’an, along with classical and contemporary exegeses, interprets and integrates these concepts within the framework of Islamic epistemology. The findings indicate that knowledge in Islam encompasses not only rational and empirical aspects, but also spiritual and moral dimensions, positioning it as a means to attain well-being in both this world and the hereafter.